Behavior and outcomes of 141 acquired lacrimal sac mucoceles treated via endoscopic dacryocystorhinostomy - Ying-Jie Ma; Guang-Ming Zhou; Zhi-Rong Liu; Jin-Fei Wei; Xin-Yu Li; Bin Dong; Lin-Juan Wu; Wen-Can Wu; Bo Yu (International Journal of Ophthalmology)
AIM: To investigate the clinical profile of patients with acquired lacrimal sac mucocele (ALSM) and evaluate the efficacy of endoscopic dacryocystorhinostomy (En-DCR) for this condition. METHODS: En-DCRs were performed on 141 patients with ALSM patients from January 2016 to March 2022. The clinical baseline information and magnetic resonance imaging (MRI) images were recorded and summarized. To assess the effectiveness of En-DCR therapy, both anatomical and functional success rate was assessed during a 12mo follow-up. RESULTS: A total of 141 patients, with a mean age of 57.70±14.11y, were enrolled in this study. Majority of the patients were female (n=91; 64.54%) and all had unilateral disease. All patients had a previous history of epiphora and purulent secretion, and the duration from lacrimal duct obstruction to mucocele formation ranged from 6 to 120mo. MRI findings consistently revealed an enlarged sac diameter, fluid accumulation separated by a thin rim from adjacent tissues, which is indicative of lacrimal sac mucocele. En-DCR was performed with an anatomical success rate of 93.62% and a functional success rate of 81.56%. CONCLUSION: ALSM is more commonly seen in females and unilaterally. It is essentially a complication of lacrimal duct obstruction. MRI characteristics can be used for precise clinical diagnosis, while En-DCR emerges as an optimal therapy for this condition. Our results provide a comprehensive reference for the diagnosis and treatment of ALSM.